SELFIE MARKETING AND CUSTOMER LOYALTY: MEDIATING ROLE OF EXPERIENTIAL SHOPPING - Octavia, Ade; Yayuk Sriayudha (Dinasti Review Publisher, 2020)
The increasing growth of modern food stalls showed a change in the behavior of consumers, especially for teenagers to fulfill the needs of a representative place to increase social activity. The purpose of this study is to analyze the effect of selfie marketing and customer loyalty with experiential shopping as a mediating role. The authors seek to understand how this selfie marketing to determine the customer loyalty of modern food stalls customer through experiential shopping. Design research using quantitative methods with the approach of the survey. Sample consumer research is the modern method of stalls that add up to 150 people. Sampling method using judgement sampling. The tools of data analysis using the method PLS. Finding suggests that experiential shopping has a significant effect on selfie marketing and experiential shopping and selfie marketing affects customer loyalty on modern food stalls.